Aligning the context of rural tourism policies in Sabah - Siow, May Ling; Ramachandran, Sridar; Nair, Vikneswaran (2012)
Rural tourism is known as an effective catalyst for rural socio-economic regeneration. This form of tourism creates employment opportunities, better income distribution, preservation of village environment and local culture. The success and the sustainability of rural tourism depend on the role of government and its agencies in shaping and governing these policies. Rural tourism in Sabah is one of the three priorities highlighted under the Sabah’s State Development Agenda. In line with Sabah Tourism Master Plan 2011-2025, the government of Sabah has drawn out a strategic development plan for tourism to catapult this industry to the next level by adding value and ensuring long-term sustainable growth. This plan is a protégé of the Tourism Master plan 1981 and Sabah Tourism Development Guidelines 1995. At present, rural tourism policies in Sabah for authorities and business operators remain ambivalent. Initial community group discussion indicates a lack of interaction between policy makers and its stakeholders highlighting gaps in the rural tourism governance resulting in conflicting policy implementation. This research aims to explore the issues, possible redundancies and loopholes of existing policies at local, state and federal level pertaining rural tourism policies. This process would first involve the identification of relevant policy documents governing rural tourism in Sabah. The analysis will include compiling, comparing and bridging the policy gaps. The complex nature governing Sabah’s Rural Tourism policy issues involve various actors at local, state and federal levels. Hence, the Actor Network Theory (ANT) is employed in developing propositions that will bridge the gap amongst the existing policies governing rural tourism.